Augmentative and alternative communication intervention in traumatic brain injury - Gómez Taibo, María Luisa; Pérez García, Eva Mª (Revista de Investigación en Logopedia, 2018)
Traumatic brain injury (TBI) survivors may experience significant communication disorders that depend on factors such as the extent and the severity of the injury, and the level of cognitive functioning. Communication disorders restrict participation in conversation and daily functional tasks and limit the reintegration to familiar, social and working environments. Communication needs that stem from these impairments are usually unmet. Hence, the Augmentative and Alternative Communication intervention is an option for consideration along recovery process to compensate for temporal or permanent communicative needs and in an attempt to maximize communication function for social interaction. The aim of this paper is to describe the variety of AAC tools and strategies for a successful AAC assessment and intervention for TBI survivors. We follow the organizational framework of interventions strategies proposed by Fager et al. (Fager, 2005; Fager & Beukelman, 2005; Fager & Karantounis, 2010; Fager, Doyle, & Karantounis, 2007) that include the Stimulation Level, Structured Level and Compensation Level, rather than the traditional phases of recovery model. This study aims to contribute to Speech and Language Therapy intervention insofar as there are no materials written in Spanish that describe and summarize the variety of AAC assessment and intervention strategies in the traumatic brain-damaged population.